A Comparative study between the efficacy of combined Intense Pulsed Light plus high-intensity focussed ultrasound in the treatment of atrophic and icepick scars - Fatima Ahmed Salem; Wisam Majeed Kattoof; Mustafa Salih Al Musawi (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the efficiency of high-intensity focussed ultrasound with intense pulsed light in the treatment of atrophic and icepick acne scars. Method: The interventional study was conducted between November 2021 and April 2022 at the Postgraduate Medical Physics Laboratory, Mustansiriyah University, Baghdad, Iraq, and comprised patients with atrophic scars in group A and acne scars in group B. They were treated first with intense pulsed light and then with high-intensity focussed ultrasound. All patients received 4 treatment sessions spread over 4 weeks. Outcome assessment was done using Patient and Observer Scar Assessment Scale. Data was analysed using SPSS software version 24. Results: Of the 22 patients, 12(55%) were males with mean age 20.75±4.20 years, and 10(45%) were females with mean age 21±2.05 years. The combination technique showed significant outcomes compared to baseline (p<0.05). Atrophic scars exhibited significantly greater improvement compared to icepick scars (p<0.05). There was no significant difference between the overall opinion of the observer (p=0.3549) and the patients (p=0.0956). Conclusion: The high-intensity focussed ultrasound and intense pulsed light techniques used in combination was found to be effective in treating atrophic and icepick scars. Key Words: Cicatrix, Acne Vulgaris, Acne scars